Suppression of Gq Function Using Intra-Pipette Delivery of shRNA during Extracellular Recording in the Ventral Tegmental Area - Nimitvilai, Sudarat; Arora, Devinder S.; McElvain, Maureen A.; Brodie, Mark S. (Frontiers in Cellular Neuroscience, 2013)
Selective suppression of protein function in the brain can be achieved using specific silencing RNAs administered in vivo. A viral delivery system is often employed to transfect neurons with shRNA directed against specific proteins, and intervals of several days are allowed between microinjection of the shRNA-containing virus into the brain and experiments to assess suppression of gene function. Here we report studies using extracellular recording of dopaminergic neurons of the ventral tegmental area (DA VTA neurons) recorded in brain slices in which lentivirus containing shRNA directed against Gq was included in the recording pipette, and suppression of Gq-related function was observed within the time frame of the recording. The action of neurotensin is associated with activation of Gq, and the firing rate of DA VTA neurons is increased by neurotensin. With shRNA directed against Gq in the pipette, there was a significant reduction of neurotensin excitation within two hours. Likewise, time-dependent dopamine desensitization, which we have hypothesized to be Gq-dependent, was not observed when shRNA directed against Gq was present in the pipette and dopamine was tested two hours after initiation of recording. As the time interval (two hours) is relatively short, we tested whether blockade of protein synthesis with cycloheximide delivered via the recording pipette would alter Gq-linked responses similarly. Both neurotensin-induced excitation and dopamine desensitization were inhibited in the presence of cycloheximide. Inclusion of shRNA in the recording pipette may be an efficient and selective way to dampen responses linked to Gq, and, more generally, the use of lentiviral-packaged shRNA in the recording pipette is a means to produce selective inhibition of the function of specific proteins in experiments.